Traffic Light Control System Using Microcontroller - Rasha falah kadhem (Al-Qadisiyah Journal of Pure Science, 2018)
Computing machines were always consided an attraction for the automation field of technology in both industrial and domestic products. For that reason, we should learn how to programed and used Microcontroller as a useful device. That led to more and more universities and colleges become interesting and starting to teach the microcontroller, especially Microchip PIC microcontrollers. This research an effort to design, programming and build a basic programmable traffic light control device for 4 tracks intersection.